1995
DOI: 10.1080/02571862.1995.10634342
|View full text |Cite
|
Sign up to set email alerts
|

The effects of tillage systems on soil bulk density and penetrometer resistance of a sandy clay loam soil

Abstract: Standard triaxial compression tests were carried out on an agricultural sandy loam soil to assess the effect of soil dry bulk density and moisture content on soil mechanical properties, namely, cohesion, internal friction angle, Young's modulus of elasticity and Poisson's ratio. Regression analyses were performed to establish mathematical relationships for simulating the variation in these mechanical properties as a function of dry bulk density and moisture content. These relationships were developed for six t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
2
6
0
1
Order By: Relevance
“…6) is consistent with data presented by Steyn et al (1995), which showed higher penetration resistance in the top 20 cm of soils under minimum tillage, compared to conventional tillage. The current data are also consistent with Steyn et al (1995) in that the differences in penetration resistance between the tillage methods were not large enough to influence root growth significantly. The penetrometer measurements did not capture potential surface crusting.…”
Section: Discussionsupporting
confidence: 82%
“…6) is consistent with data presented by Steyn et al (1995), which showed higher penetration resistance in the top 20 cm of soils under minimum tillage, compared to conventional tillage. The current data are also consistent with Steyn et al (1995) in that the differences in penetration resistance between the tillage methods were not large enough to influence root growth significantly. The penetrometer measurements did not capture potential surface crusting.…”
Section: Discussionsupporting
confidence: 82%
“…The effect was lowest in NT and RT plots and maximum in conventional tillage farmers practice (CTf) plots followed by CTm plots. Lower effects in NT and RT plots might be due to lesser degradation of organic matter compared to CTm and CTf plots [6] [27] [34]. Presence of high exchangeable Ca 2+ and Mg 2+ in soil ( Table 1) might have also contributed to formation of denser structure due to series of wetting and drying cycles before harvesting.…”
Section: Bulk Density Infiltration Rate and Soil Strengthmentioning
confidence: 99%
“…는 임도는 절성토 비탈면의 녹화에 시간이 오래 걸리는 문제가 심화되고 있으며 (Steyn and Tolmay, 1995) (Chun and Oh, 1993;Jung, 2001;Lee et al, 2003). …”
unclassified